Effect of long duration exercise on the ratings of perceived exertion and perceived diffculty of walking and running at the ventilatory threshold - Grego, F.; Collardeau, M.; Vallier, J. M.; Delignieres, D.; Brisswalter, J. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The purpose of this study was to examine if the relationship between physiological changes classically observed with exercise duration and some subjective workload measures would be affected by the complexity of the locomotion mode (running vs racewalking). METHODS: The study was conducted on 24 well trained subjects (12 long distance runners and 12 racewalkers) divided in 3 groups (runners, racewalkers and control). Energy cost of locomotion (C), heart rate (HR), minute ventilation (V(E)), lactate concentration [La], ratings of perceived exertion (RPE 6-20 scale) and ratings of perceived difficulty (RPD 1(-1)5 scale) were recorded during 2 10-min submaximal tests on a treadmill before and immediately after a 3 hour exercise (racewalking or running) conducted at the velocity ventilatory threshold (vVT). RESULTS: No significant variations in physiological parameters and perceived measures were observed in G(c). A significant increase (p<0.05) in energy cost of walking (mean: +9.4%) and running (mean: +7.5%) at the end of exercise was observed. A significant interaction of locomotion mode and exercise duration was found on perceived exertion and perceived difficulty. In racewalkers RPD significantly increased with duration whereas no significant effect was found for RPE. Conversely a significant increase in RPE was found after 3 hours in runners without any significant change in RPD. CONCLUSIONS: This experiment suggests that, for a complex task, the classical relationship between RPE and metabolic load increase during prolonged exercise could be affected by changes in RPD. In this study, stability in RPE and increase in RPD observed in racewalkers may reflect an attentional focus dissociated from internal sensations and directed toward maintaining the required race walking gait.